2021
DOI: 10.1080/13880209.2021.1953539
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin attenuates prostatic hyperplasia caused by inflammation via up-regulation of bone morphogenetic protein and activin membrane-bound inhibitor

Abstract: He (2021) Curcumin attenuates prostatic hyperplasia caused by inflammation via up-regulation of bone morphogenetic protein and activin membranebound inhibitor,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…Previous research has demonstrated that these growth factors are associated with angiogenic growth [ 20 ], stromal extracellular matrix accumulation [ 21 ] and prostatic enlargement [ 22 ] in animal BPH models. Another animal study by Liu et al found that treatment with Curcumin reduced PV by reduction of the epithelial–mesenchymal transition on histology [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research has demonstrated that these growth factors are associated with angiogenic growth [ 20 ], stromal extracellular matrix accumulation [ 21 ] and prostatic enlargement [ 22 ] in animal BPH models. Another animal study by Liu et al found that treatment with Curcumin reduced PV by reduction of the epithelial–mesenchymal transition on histology [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of the causes of prostatic inflammation, the latter is characterized by a large infiltration of T-cells and the expression of a variety of pro-inflammatory cytokines [ 24 , 25 ]. Liu et al demonstrated that administration of Curcumin in mice caused a lower expression of pro-inflammatory cytokines such as IL-6 and TNF-a as compared to the control group, indicating that Curcumin alleviates inflammation in an induced BPH mouse model [ 15 ]. The role of inflammation in BPH was also confirmed in three randomized clinical trials where non-steroidal anti-inflammatory drugs were administered in patients with LUTS/BPH in comparison with placebo for 4–24 weeks [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aberrant proliferation of stromal and epithelial cells causes glandular hypertrophy and bladder outlet obstruction [ 33 ]. Considering that EMT and the balance between epithelial proliferation and apoptosis are central events during BPH [ 34 , 35 ], m 6 A modification might act on BPH etiology and pathology by affecting these molecular and cellular events.…”
Section: Discussionmentioning
confidence: 99%
“…This conclusion has been verified in many experiments. Taking CUR as an example, CUR alleviates inflammatory diseases by reducing major markers of inflammation, such as IL-6 and TNF-α, malondialdehyde, sensitive C-reactive protein, MCP-1 ( 114 116 ). The anti-inflammatory effect of dietary polyphenols is the basis of their biological activity.…”
Section: Discussionmentioning
confidence: 99%